POTENTIOMETRIC DETERMINATION OF SOME APROTIC ACIDS IN AQUEOUS AND AQUEOUS-MIXED SOLUTIONS - Нарбек Сапаевич Палванов; Санжар Йулдашевич Дусов магистр (Journal Park Publishing, 2023)
Henderson`s method to estimate the constant acidity aprotic acids: iron (III) and aluminum (III) in water and water -mixed solvents (ethanol, propanol -1, propanol-2) 3:1. Тhe possibility of acid-base titrimetric analysis of non these aprotic acids in these solutions. Established that the, conditions of titration improved by increasing the share of non -aqueous solvent, which reduces the dielectric constant of the medium.
Keywords: аprotic acid, iron (III) chloride and sulfate, aluminum (III) chloride and sulfate, acidity constant.